High Levels of Plasma FVIII and vWF in the Toxic Epidemic Syndrome Patients - López-Fernández, M F; López-Berges, C; Fermoso, J; Martín-Pascual, A; Sánchez-Hernández, J J; López-Borrasca, A; Batlle, J (Thrombosis and Haemostasis, 1989)
Factor VIII and von Willebrand factor proteins were evaluated in 115 patients having the chronic phase of the Toxic Epidemic Syndrome (TES), a new multisystemic disease probably caused by the ingestion of denatured rapeseed oil, and in 50 control volunteers. Higher circulating levels of factor VIII procoagulant activity (VIII :C) (158 ± 58.4 U/dl), von Willebrand factor antigen (vWF: Ag) (166.1 ± 55.5 U/dl) and von Willebrand factor ristocetin cofactor activity (vWF:RCo) (178.7 ± 55.2 U/dl) were seen in TES patients (p < 0.001, TES patients versus control subjects, for each parameter). The increased levels of vWF:Ag and vWF:RCo observed in TES patients correlated with the scleroderma like lesion of the skin, with the sicca syndrome and with Raynaud's phenomenon (p < 0.01), but not with other clinical manifestations. The multimeric analysis of vWF in 92% of the TES patients was similar to that found in normal plasma, but in the remaining 8% a very slight increase of larger vWF multimers in plasma were observed. The raised levels of vWF found in TES patients in the chronic phase may reflect an “in vivo” vascular injury.
Keywords: von Willebrand factor; FVIII; Epidemic toxic syndrome; Scleroderma-like lesions